(untitled) (Italian Review of Legal History, 2020)
The paper focuses on the topic of the impact of piracy on the institutional framework in the Kingdom of Naples during the Modern Age (XVIth ̶ XVIIth centuries). Many historians agree that the continuous Ottoman̶-Barbaresque raids on the coast of Southern Italy played a key role in the conditions of fragility and weakness of the South and its progressive marginalization from the economic and productive networks of early modern Europe. Consequently, the paper first analyzes the reason for military weakness of the Kingdom of Naples, and then it examines the effect of defensive vulnerability on the political-constitutional field through a Juridical culture’s paradigmatic text: the Tractatus de potestate Proregis et Collaterali Consilii et regimine Regni by Giovan Francesco De Ponte. In hindsight, the evaluation of the strategies of the government during the Spanish viceroyalty shows how the strong alliance between the Spanish Monarchy and the lawyers-administrators (the noble of robes) was a formidable legitimizing machine for the monarchy, but it also leads to the nobility progressively moving away from its traditional role of government and military defense. The final result of this compromise was to deprive the Kingdom of the only means that they had that could effectively counter attack the maritime dominance of the Ottoman-Barabresque pirates and feed a growing sense of insecurity which deeply scarred the fragile political balances of the southern Monarchy.